2015
DOI: 10.1371/journal.pone.0141262
|View full text |Cite
|
Sign up to set email alerts
|

Zinc and Other Metals Deficiencies and Risk of Type 1 Diabetes: An Ecological Study in the High Risk Sardinia Island

Abstract: BackgroundType 1 diabetes incidence presents a decreasing gradient in Europe from the Nordic countries to the Mediterranean ones. Exception to this gradient is represented by Sardinia, the second largest Mediterranean island whose population shows the highest incidence in Europe, after Finland. The genetic features of this population have created a fertile ground for the epidemic of the disease, however, as well as being strikingly high, the incidence rate has suddenly presented a continuous increase from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…In addition, environmental factors that affect zinc levels in soil and water may be important in determining disease risk. Ecological studies have shown negative associations between zinc levels in soil and onset of autoimmune diseases, specifically Type 1 DM [49] and multiple sclerosis [50], suggesting that natural zinc bioavailability in different locations can influence risk of developing diseases. …”
Section: Discussionmentioning
confidence: 99%
“…In addition, environmental factors that affect zinc levels in soil and water may be important in determining disease risk. Ecological studies have shown negative associations between zinc levels in soil and onset of autoimmune diseases, specifically Type 1 DM [49] and multiple sclerosis [50], suggesting that natural zinc bioavailability in different locations can influence risk of developing diseases. …”
Section: Discussionmentioning
confidence: 99%
“…This is important in relation to environmental factors such as zinc in drinking water and soils. Although T1DM is clearly related to genetic factors such as HLA-DR3-DQ2 and HLA-DR4-DQ8 [ 318 ], the risk of onset of T1DM is associated with low levels of zinc in drinking water and soils [ 233 , 334 ]. Moreover, zinc deficiency triggers the IL-6-induced phosphorylation of STAT3 [ 145 ], thereby pathologically enhancing B cell differentiation into antibody-producing plasma cells and autoantibody production.…”
Section: Zinc Deficiency In the Context Of Diseasementioning
confidence: 99%
“…We found a small but significant negative association between type 1 diabetes and lead in soil in our EnWAS and Bayesian analyses, although this association did not remain significant in the multivariable ecological regression. A study in Sardinia reported a significant negative correlation between type 1 diabetes incidence rates and lead in stream sediments [42].…”
Section: Discussionmentioning
confidence: 98%